"Clothed with poetry:" Lafcadio Hearn's decadent aesthetics of translation - Evangelista, S-M (University of Chicago Press, 2023)
In Europe, the late nineteenth century was marked by an explosion of interest in Japanese arts and culture known as japonisme. While japonisme flourished, however, translations of Japanese literature remained extremely limited. This article explores the contribution of Lafcadio Hearn (1850–1904) to the diffusion of Japanese literature in translation, arguing that his works represent a pioneering effort to circulate Japanese literature internationally through the framework of decadence. Focusing in particular on the collection Shadowings (1900), the article suggests that Hearn’s Japanese essays and stories drew on ideas and literary techniques associated with decadent literature in the West and fed, in their turn, a decadent fascination with the exotic, the uncanny, and the relationship between literature and the visual arts. In Shadowings, Hearn suggestively presented translation as an art of shadows, a metaphor that interacted with the theme of the Japanese uncanny while looking back to Théophile Gautier’s definition of decadent aesthetics. Hearn made a highly creative use of translation by mixing different translational forms, ranging from the transliteration of isolated words to entire versions of Japanese source texts. His writings also frequently dramatized encounters with translation in order to present translation as an embodied and collaborative practice involving a network of social relations. In this process, translation shaped not only his cultural and social interactions with Japan but also his self-knowledge as cultural mediator.